VD_FINDINFO MP / 2021 / 5 vom 13. Juli 2021 - VD Tribunal cantonal (2021)
FIDÉLITÉ, INCITATION À VIOLER OU À RÉSILIER UN CONTRAT, DÉBAUCHAGE | 321a CO, 678 al. 2 CO, 2 LCD, 4 let. a LCD, 9 al. 2 LCD, 128 al. 1 CPC (CH), 132 CPC (CH), 152 al. 2 CPC (CH)